A Study to Assess the Effectiveness of Structured Teaching Programme on Knowledge Regarding Updated National Immunization Schedule among the Postnatal Mothers Visiting Health Centre - Tejashri Ligade1 , Sagar Kulkarni2 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Youngsters are an epitome of our fantasy. They are the most defenceless gathering in the general public.So kids require unique consideration to have a great wellbeing. Thus youngsters require good attention tohave a better well-being. 1Immunization, specifically has spared a huge number of youthful lives and withappropriate use.1 The IAP committee on immunization has classified some vaccine as optional vaccinee.g. Hepatitis A, Hb vaccine, varicella, Pneumococcal vaccine, typhoid vaccine, IPV. Optional vaccinefor personal use depends on occurrence of the contamination and illness, age, sickness and possibility ofillness in vulnerable person when receiving of vaccine prompted immunity and the result of immunisationis assessed on volunteered immunization in the national immunization programme. Now hepatitis B vaccineis only the one which is considered.2Methods: A true experimental study design using pre-test as well as post-test with no control group. Thedata composed with 30 postnatal mothers under non probability convenient sampling technique to know theefficiency of structured teaching plan on knowledge about Updated National Immunization Schedule.Pre-test was done among postnatal mother with closed ended survey questions. Soon after pre-test structuredteaching programme on awareness about Updated National Immunization Schedule was given to thepostnatal mothers. Evaluation was be done by conducting post-test on the same day of the operation byusing same closed ended questionnaire which was used for pre-test.Results: Findings reflected, many of the postnatal women (43.33%) were in 20-25 years. Highest percentage70% of postnatal mother was housewife. 66.67% of postnatal mother were completed primary education.70% postnatal mothers are from middle class family. During pre-test 30% postnatal mother had moderatelyadequate knowledge and 70% postnatal mother had inadequate knowledge whereas, during post-test 73.33%postnatal mother had adequate knowledge, 26.67% postnatal mother had moderate adequate knowledge.Conclusion: The study demonstrated that the structure teaching program about Updated NationalImmunization programme in the postnatal mothers going to wellness centre, was effective to improve theknowledge of postnatal mothers.